Dimensión Práctica del Examen Complexivo Previo a la Obtención del Grado Académico de Licenciada en Enfermería - Arana Litardo, Vanessa Jacqueline (2018)
In this present case study, I try to obtain excellent results with the nursing care with the diagnosis of Gastroschisis, for which it was operated surgically, this process takes constancy and permanence in the follow-up of the neonate. Gastroschisis is a congenital anomaly evidenced by umbilical protrusion of the right side of the stomach, this disease can be treated in the pregnant woman in the 14th week of gestation with ultrasounds and complementary exams that it takes in the medical control of the pregnant woman. But in my present clinical case the mother had no medical control, her spouse consumed psychotropic substances (alcohol, drugs), the birth was evidenced by a pre-term spontaneous physiological delivery with the aforementioned diagnosis. The main objective is to apply the nursing care process to the newborn with diagnosis of Gastroschisis to obtain a satisfactory recovery in the "Matilde Hidalgo de Procel" hospital. Finalizing the case study in one way or another should take into account many nursing interventions to avoid any risk that threatens the recovery of the newborn, after the surgical intervention.